Penanggulangan Penyebaran Radikalisme Melalui Media Sosial dalam Hukum Pidana Indonesia - Kurniawan Tri WIbowo; Wahyu Hadiningrat (Jurnal Hukum Lex Generalis, 2023)
Social media is now an important factor in the spread of radicalism in Indonesia, this is supported by the use of the internet which shows an increasing trend in Indonesia. This study aims to examine the regulation of the spread of radicalism in Indonesian criminal law, analyze policies to counter radicalism carried out through social media in Indonesia. In addition, it also builds the concept of a criminal policy to combat the spread of radicalism through social media in Indonesia. The results of the study state that the regulation of the spread of radicalism carried out through social media has not been comprehensively regulated in Indonesian positive law. Efforts to combat radicalism carried out through social media in Indonesia are currently focused on repressive law enforcement. The concept of criminal policy to combat the spread of radicalism carried out through social media in Indonesia is carried out through three points of overcoming radicalism through social media, namely supervision, action and collaboration between platforms and the community. The action taken is of course not only limited to taking down content on social media but also an assessment to determine the level of radicalization of the perpetrators.